2021
DOI: 10.1088/1742-6596/1806/1/012142
|View full text |Cite
|
Sign up to set email alerts
|

Repackaging RADEC learning model into the online mode in science class

Abstract: This study aims to formulate the RADEC learning model with full online learning mode in natural science instruction, both through synchronous and asynchronous communications. This research belongs to the type of qualitative description with the participants involved consisting of 20 students and 5 teachers taken based on a purposive sampling technique. The instruments used were a questionnaire and unstructured interviews that were processed with triangulation techniques. The results of this study indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 6 publications
3
17
0
6
Order By: Relevance
“…Wahab and Iskandar (2020) observed fewer good outcomes, stating that students struggled with the tactics used and that it became a difficulty for teachers to organize effective virtual learning experiences. Sukardi et al (2020) discovered that teachers had difficulties with IDMEC teaching strategies that would innovate for basic concepts for teaching the design process content curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wahab and Iskandar (2020) observed fewer good outcomes, stating that students struggled with the tactics used and that it became a difficulty for teachers to organize effective virtual learning experiences. Sukardi et al (2020) discovered that teachers had difficulties with IDMEC teaching strategies that would innovate for basic concepts for teaching the design process content curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Wahab & Iskandar's (2020) findings revealed that students struggled with the tactics used, making it difficult for teachers to organize a good virtual learning experience. Sukardi et al (2020) also observed that teachers were having difficulties with their new teaching strategies that would innovate for basic principles for teaching curriculum of specific subject, such as the design process content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to being a moderator, the teacher can act as a presenter if in this activity all students cannot answer questions asked by other students, and provide reinforcement regarding the concept of the material being discussed, and respond to student opinions. This stage trains students to be able to have communicative thinking skills so that students can communicate the results of group discussions that have been carried out at a later stage (Sukardi, et al, 2021). Activities at this stage foster student character to be confident in delivering the results of the discussion.…”
Section: Infusion Of Environment Dimension Of Esd Into Science Learning Through the Radec Learning Modelmentioning
confidence: 99%
“…The development of learning in this ZPD area is an effort to realize quality education for all students with a variety of abilities, from students who need guidance to students with high cognitive abilities. The RADEC model has student-centered learning steps and encourages students to be able to develop their abilities both knowledge, skills, and attitudes holistically and comprehensively (Sopandi, 2019) and become a solution in the application of science learning in online learning mode (Sukardi, et al, 2021). This can be seen from several research results related to the implementation of the RADEC model, including (1) Pratiwi, et al, (2018) suggesting that the RADEC learning model can develop students' conceptual understanding of global warming material, the hypothesis test (t-test) is p (0.00) <0.05, there is a difference between a class using the RADEC learning model and a class that does not use the RADEC learning model; (2) Karlina, et al, (2020), examined the RADEC model in developing students 'critical thinking skills, the results showed that there were significant differences in students' critical thinking skills in the material properties of light before and after learning; (3) Sopandi, et al, (2020) stated that the RADEC model can develop students 'creative thinking abilities, the results obtained are significant increases in students' creative thinking abilities for each indicator of creative thinking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the COVID-19 pandemic conditions that demand the transformation of online learning, RADEC learning has high flexibility to be designed both in face-to-face learning, blended learning, and full online learning with a note that this repackaging must still pay attention to essential things such as the curriculum. and the support capacity of qualified human resources (Sukardi et al, 2021), so that learning can adapt well according to conditions. However, this research does not forget the direct learning that is usually done in schools in general during the pandemic as a comparative study in looking at differences in learning achievement focused on students' MCU.…”
Section: Introductionmentioning
confidence: 99%